The paradigm of systemic complexity and the sustainability of Homeland Earth: an epistemological view of the Brazilian reality according to the ideas of Edgar Morin (Acta Scientiarum. Human and Social Sciences, 2021)
The environmental issue has been built on numerous epistemological and paradigmatic biases, which now reflect the concern with the perpetuation of environmental autopoiesis, and now evidence the asymmetries revealed by the contradictions of stateless capitalism. Edgar Morin, in his various works, exposed the profound nature of the environmental system, based on a careful analysis centered on the principles of reparadigmatization. Starting from this context, the objective of this article was to understand the bases of sustainability by integrating the structuring concepts of eco-organization and environmental complexity, traced by the Moranian paradigm, and their relationship with Brazilian environmental policies. Based on the profound content analysis of the works of this epistemic protagonist, it can be inferred that the paradigm of systemic complexity is not only essential for rethinking the environmental issue in contemporary times, but it is also absolutely possible, as attested by case studies of rural peoples and communities in the State of Amazonas, located in the Brazilian Amazon, here presented. Nevertheless, this article concludes that in order to overcome the supposed dichotomy between economics and the environment and to carry out another ‘via’ on Homeland Earth, it will be necessary to build a network of solidarity and cooperation between the different actors/subjects/institutions.